Wool Wax Extraction From Washing Effluent and Effect on Olea europea Germination and Growth - Nadhem Aissani; Makrem Ghidaoui; Hichem Sebai (SAGE Publishing, 2022)
Effluents from textile industry using wool pose serious environmental nuisances in Tunisia that are mainly due to their pollutant load and the release of unpleasant odors. In order to minimize these hazards and to take advantage of these wastes for the sake of our environment, the present work consists on valuating wool wax from washing effluent on olive ( Olea europea ), germination and growth. Extraction was made in water at 70°C or hexane using sonication followed by concentration of the extracts in soxhlet apparatus. Results showed that this waste is characterized by its richness in total lipid content with extraction yields of 60.7 and 95.6%, respectively. GC-MS analysis of wax showed its richness on fatty acids. Six saturated fatty acids ranking from 15 to 27 carbon atoms were characterized. Furthermore, diluted wax at a dose of 1.25 mg/g significantly improves germination of olive seeds by germination index calculation, to reach a maximum of 150 ± 17%. In fertigation experiment, the use of the same dose of diluted wax promotes plant length to reach 45.7 ± 2.52 cm. GC-MS analysis after derivatization showed significant enhancement of auxin production in plants treated with 1.25 mg of wax/g of soil compared to control with a concentration of 1.1 ± .1 and .7 ± .2 ng/mg, respectively. This leads us to valuate wool wax as environmental friendly natural product in agricultural and fertigation practice of olive plant.